Assembling the archaeal ribosome: roles for translation-factor-related GTPases. (19th January 2011) - Blombach, Fabian; Brouns, Stan J.J.; van der Oost, John
Abstract : The assembly of ribosomal subunits from their individual components (rRNA and ribosomal proteins) requires the assistance of a multitude of factors in order to control and increase the efficiency of the assembly process. GTPases of the TRAFAC (translation-factor-related) class constitute a major type of ribosome-assembly factor in Eukaryota and Bacteria. They are thought to aid the stepwise assembly of ribosomal subunits through a 'molecular switch' mechanism that involves conformational changes in response to GTP hydrolysis. Most conserved TRAFAC GTPases are involved in ribosome assembly or other translation-associated processes. They typically interact with ribosomal subunits, but in many cases, the exact role that these GTPases play remains unclear. Previous studies almost exclusively focused on the systems of Bacteria and Eukaryota. Archaea possess several conserved TRAFAC GTPases as well, with some GTPase families being present only in the archaeo–eukaryotic lineage. In the present paper, we review the occurrence of TRAFAC GTPases with translation-associated functions in Archaea.